Self-Commodification Of University Students In Tiktok Content: A Visual And Verbal Semiotic Analysis - Eni Novita; Irene Julianti; Martha Heriniazwi Dianthi (Multidisciplinary Journals, 2026)
This study examines the process of self commodification among Indonesian migrant university students through TikTok content using a visual and verbal semiotic analysis. As economic pressures increase, many students living away from their hometowns utilize TikTok as an alternative source of income by transforming personal identity, emotions, and everyday experiences into monetizable content. This research employs a qualitative approach grounded in Roland Barthes’ semiotic framework, focusing on denotation, connotation, and myth to interpret meanings embedded in student generated TikTok videos. The findings indicate that self commodification is constructed through recurring visual and verbal signs that depict ordinary student life while simultaneously conveying struggle, authenticity, and perseverance. At the mythological level, these representations normalize digital labor and frame self commodification as a natural and acceptable strategy for economic survival. The study highlights how TikTok functions not only as a communication platform but also as a space where identity performance and economic necessity intersect. This research contributes to communication studies by providing a critical understanding of meaning making, digital labor, and identity construction among Indonesian migrant university students.